2012
DOI: 10.1126/science.337.6094.510
|View full text |Cite
|
Sign up to set email alerts
|

Multicellularity Driven by Bacteria

Abstract: Bacteria can prompt single-celled choanoflagellates to divide into multicellular versions of themselves, biologists reported last week at the 71st annual meeting of the Society for Developmental Biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Eine andere Frage, die durch die Herstellung von Hybridsequenzen aus einzelligen und einfachen mehrzelligen Organismen untersucht werden kann, betrifft die Evolution einzelliger Organismen zu komplexen Lebensformen. Zum Beispiel wurden einzellige und koloniale Choanoflagellate sowie deren Beziehung zu bakteriellen Lebensformen studiert, um Einblicke in die Entstehung von Mehrzelligkeit zu gewinnen . Allerdings könnte die Synthese und Assemblierung von Hybridgenomen klarere Einblicke in die evolutionäre Aufspaltung zellulärer Funktionen bieten.…”
Section: Genomsynthese Als Methode In Der Evolutionsforschungunclassified
“…Eine andere Frage, die durch die Herstellung von Hybridsequenzen aus einzelligen und einfachen mehrzelligen Organismen untersucht werden kann, betrifft die Evolution einzelliger Organismen zu komplexen Lebensformen. Zum Beispiel wurden einzellige und koloniale Choanoflagellate sowie deren Beziehung zu bakteriellen Lebensformen studiert, um Einblicke in die Entstehung von Mehrzelligkeit zu gewinnen . Allerdings könnte die Synthese und Assemblierung von Hybridgenomen klarere Einblicke in die evolutionäre Aufspaltung zellulärer Funktionen bieten.…”
Section: Genomsynthese Als Methode In Der Evolutionsforschungunclassified
“…Another question that can be addressed by generating hybrid sequences of unicellular with simple multicellular organisms is the evolution of single-cell organisms to complex life forms.W ork on unicellular and colonial choanoflagellates and their relationship with the bacterial life forms is one of the directions being explored as to how multicellularity arose. [80] However,h ybrid genome synthesis and assembly could shed more light on the division of cellular functions. Taken together these research directions taken in parallel with significant ethical discussions and considerations,w ill usher in the transition from mostly molecular to testable organismic evolution.…”
Section: Reviewsmentioning
confidence: 99%
“…When such organisms emerged on Earth several millions of years ago, the planet was already crowded with microbial life. Consequently, the emergence and evolution of plants and animals were not only carried out in the presence of microbes but, in many cases, such evolution was only possible because of these microorganisms (Zilber- Rosenberg and Rosenberg, 2008;Alegado et al, 2012;Carpenter, 2012;Gaulke et al, 2016). Recent studies have unequivocally shown that there is a great variety of microbes living in plant and animal hosts, the totality of which is known as the host's microbiota.…”
mentioning
confidence: 99%